TRANSITION TO GENERAL STUDY IN SOVIET UKRAINE (30th years of the ХХ century): TRUE AND FALSENESS - Мандрик, Я. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the research work there have been Soviet considered the problems connected with the transition to the general education in the Soviet Ukraine. The final terms of this transition have been investigated as well. Profound evidence has shown that this activity took place only within 1937 – 1938.